Abnormal synergies and associated reactions post-hemiparetic stroke reflect muscle activation patterns of brainstem motor pathways - McPherson, Laura M.; Dewald, Julius P. A. (Frontiers in Neurology, 2022)
Individuals with moderate-to-severe post-stroke hemiparesis cannot control proximal and distal arm independently because they are constrained to stereotypical movement patterns called the flexion and extension synergies. Accumulating evidence indicates that these synergies emerge because of upregulation of diffusely-projecting brainstem motor pathways following stroke-induced damage to corticofugal pathways. During our recent work on differences in synergy expression among proximal and distal joints (1), we serendipitously observed some notable characteristics of synergy-driven muscle activation. It seemed that: paretic wrist/finger muscles were activated maximally during contractions of muscles at a different joint; differences in the magnitude of synergy expression occurred when elicited via contraction of proximal vs. distal muscles; and associated reactions in the paretic limb occurred during maximal efforts with the non-paretic limb, the strength of which seemed to vary depending on which muscles in the non-paretic limb were contracting. Here we formally investigated these observations and interpreted them within the context of the neural mechanisms thought to underlie stereotypical movement patterns. If upregulation of brainstem motor pathways occurs following stroke-induced corticofugal tract damage, then we would expect a pattern of muscle-dependency in the observed behaviors consistent with such neural reorganization. Twelve participants with moderate-to-severe hemiparetic stroke and six without stroke performed maximal isometric torque generation in eight directions: shoulder abduction/adduction and elbow, wrist, and finger flexion/extension. Isometric joint torques and surface EMG were recorded from shoulder, elbow, wrist, and finger joints and muscles. For some participants, joint torque and muscle activation generated during maximal voluntary contractions were lower than during maximal synergy-induced contractions (i.e., contractions about a different joint), particularly for wrist and fingers. Synergy-driven contractions were strongest when elicited via proximal joints and weakest when elicited via distal joints. Associated reactions in the wrist/finger flexors were stronger than those of other paretic muscles and were the only ones whose response depended on whether the non-paretic contraction was at a proximal or distal joint. Results provide indirect evidence for the influence of brainstem motor pathways on abnormal motor behaviors post-stroke, and they demonstrate the need to examine whole-limb behavior when studying or seeking to rehabilitate the paretic upper limb.